Case report: A patient with EGFR L861Q positive adenosquamous lung carcinoma transforming into large cell neuroendocrine cancer after treatment with Almonertinib - Cheng, Kele; Zhu, Yong; Sang, Ran; Kuang, Zhongsheng; Cao, Yang (Frontiers in Oncology, 2025)
Almonertinib, a third-generation epidermal growth factor receptor tyrosine kinase inhibitor, is selective for both epidermal growth factor receptor tyrosine kinase inhibitor–sensitizing and T790M resistance mutations. However, resistance to the third-generation EGFR-TKIs is still inevitable. Econdary EGFR mutations, and bypass pathway activation have been reported with Almonertinib therapy. This article presents a rare case report of a patient with EGFR L861Q positive adenosquamous lung carcinoma who transformed into large cell neuroendocrine carcinoma following treatment with Almonertinib. The patient exhibited disease progression 8 months after initiating Almonertinib treatment, and a blood genetic test revealed mutations in EGFR L861Q and EGFR L858R. A subsequent lung biopsy after progression confirmed the diagnosis of large cell neuroendocrine carcinoma, and subsequently treatment with cisplatin and etoposide was effective. Transformation into neuroendocrine carcinoma is one of the mechanisms behind resistance to Almonertinib in adenosquamous lung carcinoma. EGFR mutations may persist even after transformation into neuroendocrine carcinoma. For non-small cell lung cancer patients undergoing Almonertinib therapy, this case report emphasizes the importance of performing a timely pathological biopsy upon the emergence of resistance.